2021
DOI: 10.1002/pne2.12065
|View full text |Cite
|
Sign up to set email alerts
|

Toward personalized medicine for pharmacological interventions in neonates using vital signs

Abstract: Vital signs, such as heart rate and oxygen saturation, are continuously monitored for infants in neonatal care units. Pharmacological interventions can alter an infant's vital signs, either as an intended effect or as a side effect, and consequently could provide an approach to explore the wide variability in pharmacodynamics across infants and could be used to develop models to predict outcome (efficacy or adverse effects) in an individual infant. This will enable doses to be tailored according to the individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…They encompass predictive modelling, spanning length of stay, disease severity, and mortality risk, contributing to a deeper understanding of neonatal conditions. These studies deepen the comprehension of neonatal conditions and their determinants, aligning with the literature's focus on advancing scientific understanding and medical care in the NICU (43,(61)(62)(63)(64)(65)(66).…”
Section: Discussionmentioning
confidence: 72%
“…They encompass predictive modelling, spanning length of stay, disease severity, and mortality risk, contributing to a deeper understanding of neonatal conditions. These studies deepen the comprehension of neonatal conditions and their determinants, aligning with the literature's focus on advancing scientific understanding and medical care in the NICU (43,(61)(62)(63)(64)(65)(66).…”
Section: Discussionmentioning
confidence: 72%
“…34 This highlights the need for sharing physiological and neonatal outcome data; developing a consensus of a standardized format for data sharing is important to facilitate these aims. 13 The NEDROP2 study and a large Swiss study reported that, respectively, 39 out of 1085 (3.6%) and 94 out of 7817 (1.2%) fully screened infants received treatment for developing ROP. 35,36 This is lower compared to the 14% of infants in our study who required laser treatment, probably because our study population is not fully comparable to these studies which included infants born at both high-care and regional centers and highlights the likely need to include infants from lower-care settings to create a model that will be accurate in all centers.…”
Section: Discussionmentioning
confidence: 99%
“…Although the obtained physiological monitor data are used to detect trends and identify severe episodes of physiological instability, this snapshot method means that these data are often not used to their full potential and opportunities to improve clinical management may be missed. [13][14][15] Analyzing physiological data could potentially lead to the identification of meaningful patterns that would otherwise be difficult or even impossible to identify, and may enable the prediction of individual risk for ROP. Previously Sullivan et al investigated whether measures of heart rate and SpO 2 in the first 7 days of life can improve predictions of mortality and morbidity in very low birth weight infants.…”
Section: Introductionmentioning
confidence: 99%
“…All four studies showed changes in the EEG with the use of respiratory stimulants, but further work is needed to ascertain whether and how these changes are related to other factors, such as age, dose, and comorbidities, and to understand how these changes in EEG might affect brain development. Understanding the effect of respiratory stimulants on brain activity may help drive individualised drug dosing in infants ( Hartley, 2021 , Hartley et al, 2021 , Kumar et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%